Storytelling e sua relação com o engajamento de stakeholders: um experimento no contexto de uma instituição pública de ensino - Ciello, Renata Romanzini (2024)
This work aims to analyze the relationship between the use of storytelling technique and engagement of stakeholders in a public organization. The research is classified as causal and quantitative, using experimental research as a methodological approach. An experiment was carried out in a scenario format as a stimulus for analysis, with an experimental design (Between-subjects). The literature used was based on Stakeholder Theory and Narrative Theory, especially to measure engagement, an adapted scale was used, based on three dimensions: affective commitment, positive affectivity and empowerment. Based on these dimensions, a research instrument was developed, submitted to expert evaluation and, after the suggested corrections, it underwent pre-testing. Subsequently, the instrument was applied to stakeholders of the chosen public institution, the Federal Institute of Education, Science and Technology of Rio Grande do Sul (IFRS), including teachers, administrative technicians in education and students. Data were analyzed using ANOVA. Analysis of the collected data confirmed the proposed hypothesis that a communication strategy that employs the storytelling technique promotes stakeholder engagement in the organization's actions. Thus, the use of storytelling emerges as a communication strategy tool to achieve effectiveness in public management related to engagement.